A Spectroscopic Study on Secondary Structure and Thermal Unfolding of the Plant Toxin Gelonin Confirms Some Typical Structural Characteristics and Unravels the Sequence of Thermal Unfolding Events - Andrea Scirè; Fabio Tanfani; Alessio Ausili (Toxins, 2019)
Gelonin from the Indian plant Gelonium multiflorum belongs to the type I ribosome-inactivating proteins (RIPs). Like other members of RIPs, this toxin glycoprotein inhibits protein synthesis of eukaryotic cells; hence, it is largely used in the construction of immunotoxins composed of cell-targeted antibodies. Lysosomal degradation is one of the main issues in targeted tumor therapies, especially for type I RIP-based toxins, as they lack the translocation domains. The result is an attenuated cytosolic delivery and a decrease of the antitumor efficacy of these plant-derived toxins; therefore, strategies to permit their release from endosomal vesicles or modifications of the toxins to make them resistant to degradation are necessary to improve their efficacy. Using infrared spectroscopy, we thoroughly analyzed both the secondary structure and the thermal unfolding of gelonin. Moreover, by the combination of two-dimensional correlation spectroscopy and phase diagram method, it was possible to deduce the sequence of events during the unfolding, confirming the typical characteristic of the RIP members to denature in two steps, as a sequential loss of tertiary and secondary structure was detected at 58 °C and at 65 °C, respectively. Additionally, some discrepancies in the unfolding process between gelonin and saporin-S6, another type I RIP protein, were detected.